2022
DOI: 10.1002/ijgo.14518
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of musculoskeletal pain among gynecologic surgeons performing laparoscopic procedures: A systematic review and meta‐analysis

Abstract: Objective Musculoskeletal discomfort is associated with repetitive movements and constrained body positions. The current meta‐analysis was performed to determine the global prevalence of musculoskeletal symptoms among gynecologic surgeons who perform laparoscopy. Methods Sources included Embase, MEDLINE, PubMed, CINAHL, Web of Science Core Collection, Cochrane Central Register of Controlled Clinical Trials, and Google Scholar. Articles published between 1980 and 2022 were considered. Studies that assessed self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…A recent meta-analysis found that over 80% of gynecologic surgeons who perform laparoscopy reported musculoskeletal symptoms, with 30% seeking treatment and 3% requiring work-hour modifications. 7 One study on laparoscopic device use, including LigaSure TM , ENSEAL TM , and Harmonic scalpel, found that more women than men reported physical complaints and inappropriate device fit. However, this difference was no…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis found that over 80% of gynecologic surgeons who perform laparoscopy reported musculoskeletal symptoms, with 30% seeking treatment and 3% requiring work-hour modifications. 7 One study on laparoscopic device use, including LigaSure TM , ENSEAL TM , and Harmonic scalpel, found that more women than men reported physical complaints and inappropriate device fit. However, this difference was no…”
Section: Discussionmentioning
confidence: 99%
“…This ergonomic advantage can lead to improved surgical precision. A recent systematic review and meta-analysis revealed that 82% of gynecological surgeons performing laparoscopic procedures experience musculoskeletal symptoms [28]. Lengthy or complex procedures such as sacrocolpopexy, for example, may be more likely to cause such symptoms.…”
Section: Advantages Of Ras For Surgeonsmentioning
confidence: 99%
“…Studies evaluating the pain prevalence among laparoscopic surgeons are rife in the literature; there are also multiple reviews on the matter [ 1 3 ]. However, more nuance is required to draw meaningful conclusions from this data.…”
Section: Introductionmentioning
confidence: 99%